Students' Learning Interest Using Web-Based Assessment at The Elementary School Level - Husni Sabil; Asrial; Syahrial; Dwi Agus Kurniawan; Rahmat Perdana; Ahmad Mansur Nawahdani; Bob Widodi (Universitas Pendidikan Ganesha, 2023)
The importance of students' interest in learning needs to be analysed to determine how influential the interest in learning is in the learning process. This study aims to analyze the effect of students' learning interest on the use of web-based assessment in elementary schools. The research method used is a quantitative method with associative causal design. The sample in this research is elementary school students. The sampling technique used is simple random sampling. The data in this study were obtained by distributing questionnaires using a liket scale. The data analysis technique used in this study was descriptive and inferential statistics. The results obtained in this study through the regression test obtained the result that there was a significant influence between students' learning interest on the use of web-based assessment of elementary school students. The conclusion in this study is that there is a positive influence between learning interest on the use of web-based assessment of elementary school students. So that the higher the interest in learning, the greater the enthusiasm of students in using web-based assessment.